THE IMPACT OF CHATGPT ON MODERN LINGUISTICS AND THE CHALLENGES IT POSES - Normamatova Zakhro Dilshodovna (Modern American Journals, 2025)
This article explores the influence of ChatGPT, a leading generative language model developed by OpenAI, on modern linguistics. It examines how ChatGPT is reshaping linguistic theories in syntax, semantics, pragmatics, and discourse, as well as its applications in computational linguistics and language pedagogy. At the same time, the paper discusses ethical and methodological challenges such as bias, grounding, and over-reliance. Drawing on recent scholarly perspectives, this paper aims to evaluate both the potential and limitations of large language models (LLMs) like ChatGPT in contemporary linguistic research and practice.
Keywords: ChatGPT, modern linguistics, syntax, semantics, pragmatics, computational linguistics, AI bias, large language models, language pedagogy